La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

L’avenir. Les changements que les personnes répondantes souhaitent voir concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

L’état des choses. Le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Le suivi. Dénonciation, soutien et qui cause le préjudice? Concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision. - Aftermetoo (2021)
Keywords: Pas de lien web

Les dommages. Les répercussions sur les personnes survivantes du harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Principaux constats. Résultats de la toute première enquête sur le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Sur le terrain. La parole aux personnes survivantes. Suggestions écrites concernant le harcèlement sexuel en milieu de travail dans les domaines des arts de la scène, du cinéma et de la télévision - Aftermetoo (2021)
Keywords: Pas de lien web

Do We Really Want to Keep the Gate Threshold That High? - Brooks, Grace; Pras, Amandine; Elafros, Athena; Lockett, Monica (Journal of the Audio Engineering Society, 2021)
Drawing upon the survey instruments of Lewis and Neville [1], Nadal [2], and Yang and Carroll [3], we conducted an online survey that captured experiences of discrimination and microaggressions reported by 387 recording engineers, producers, and studio assistants living in 46 different countries. Our statistical analyses reveal highly significant and systemic gender inequalities within the field, e.g., cisgender women experience many more sexually inappropriate comments (p < e-14, large effect size) and unwanted comments about their physical appearance (p < e-12, large effect size) than cisgender men, and they are much more likely to face challenges to their authority (p < e-13, large effect size) and expertise (p < e-10, large effect size). A comparison of our results with a study about women’s experiences of microaggressions within STEM academia [3] indicates that the recording studio workplace scores 33% worse on the silencing and marginalization of women, 33% worse on gender-related workplace microaggressions, and 24% worse on sexual objectification. These findings call for serious reflection on the part of the community to progress from awareness to collective action that will unlock the control room for women and other historically and systemically marginalized groups of studio professionals.

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.

Les chemins de ma liberté - Simard, Nathalie (Éditions des Intouchables, 2015)

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Listening to/at/with Marilyn Lerner’s "They’re All in Families" - McNeilly, Kevin (Critical Studies in Improvisation / Études critiques en improvisation, 2008)
Marilyn Lerner’s audio-art composition “They’re All in Families” (1998) re-works a sound clip from a virulently homophobic message left on an answering machine, turning hate-speech back on itself to expose the rhythms and textures of verbal violence.

C'était du spectacle! L'histoire des artistes transsexuelles à Montréal, 1955-1985 - Namaste, Viviane (McGill-Queen's University Press, 2005)
Le quartier chaud de Montréal a fait couler beaucoup d'encre, mais sa culture de cabaret n'a jamais été examinée dans la perspective des artistes transsexuelles et travesties qui l'ont rendu si populaire. Par le biais des récits provenant des danseuses elles-mêmes, Viviane Namaste peint un portrait honnête de quatorze transsexuelles - danseuses, chanteuses, magiciennes ou effeuilleuses - et jette un regard dans les coulisses du monde dans lequel vivent et travaillent ces hommes devenus femmes. Les années soixante et soixante-dix ont été des décennies de changement social au Québec. C'était du spectacle! raconte l'histoire de la première génération de transsexuelles ayant subi une chirurgie d'inversion de sexe. Namaste examine les conditions de travail dans les cabarets, la prostitution, les abus de pouvoir des policiers à l'égard des transsexuelles, le rôle du crime organisé dans la vie nocturne de la ville et l'accès aux soins de la santé. C'était du spectacle! offre un rare survol de la culture urbaine de Montréal, présenté dans ses propres mots par l'une de ses plus importantes communautés artistiques.

Briser le silence. Nathalie - Vastel, Michel (Éditions Libre Expression, 2005)
Un livre attendu, celui de Nathalie Simard, une jeune femme courageuse qui est devenue le symbole de toutes les femmes abusées, dont Michel Vastel signera l’histoire. Un témoignage touchant écrit par un journaliste d’envergure qui racontera l’histoire d’une femme, mais aussi celle de sa famille et de son entourage tout au long des années où elle a travaillé dans le monde du spectacle. Il y sera question de son enfance, son adolescence, jusqu’au dénouement médiatique de son histoire qui a éclaté dans les journaux en 2004 et en 2005.

Pretty in Punk: Girls' Gender Resistance in a Boys' Subculture - Leblanc, Lauraine (Rutgers University Press, 1999)
Pretty in Punk combines autobiography, interviews, and sophisticated analysis to create the first insider's examination of the ways punk girls resist gender roles and create strong identities.Why would an articulate, intelligent, thoughtful young women shave off most of her hair, dye the remainder green, shape it into a mohawk, and glue it onto her head? What attracts girls to male-dominated youth subcultures like the punk movement? What role does the subculture play in their perceptions of themselves, and in their self-esteem? How do girls reconcile a subcultural identity that is deliberately coded “masculine” with the demands of femininity?Research has focused on the ways media and cultural messages victimize young women, but little attention has been paid to the ways they resist these messages. In Pretty in Punk, Lauraine Leblanc examines what happens when girls ignore these cultural messages, parody ideas of beauty, and refuse to play the games of teenage femininity. She explores the origins and development of the punk subculture, the processes by which girls decide to “go punk,” patterns of resistance to gender norms, and tactics girls use to deal with violence and harassment.Pretty in Punk takes readers into the lives of girls living on the margins of contemporary culture. Drawing on interviews with 40 girls and women between the ages of 14-37, Leblanc examines the lives of her subjects, illuminating their forms of rebellion and survival. Pretty in Punk lets readers hear the voices of these women as they describe the ways their constructions of femininity—from black lipstick to slamdancing—allow them to reject damaging cultural messages and build strong identities. The price they pay for resisting femininity can be steep—girls tell of parental rejection, school expulsion, institutionalization, and harassment. Leblanc illuminates punk girls' resistance to adversity, their triumphs over tough challenges, and their work to create individual identities in a masculine world.
Keywords: Family & Relationships / Life Stages / Adolescence; Social Science / Popular Culture; Social Science / Women's Studies

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.